Determinants of Green Purchase Behavior of Local Coffee Shop: The Moderating Impact of Price Sensitivity - Nadhita Az-Zahrah; Donni Junipriansa; Joko Rizkie Widokarti (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: Indonesia has a significant plastic waste problem, despite increasing consumer awareness of environmental issues. This highlights the need for further research into factors influencing green purchase behavior (GPB), especially within the rapidly growing coffee shop sector. As coffee consumption surges, local coffee shops like Point Coffee Yogyakarta have grown substantially. Purpose: This study aimed to examine how Theory of Planned Behavior (TPB) factors influence green purchase intentions at Point Coffee Yogyakarta, while considering the moderating role of price sensitivity in the relationship between intentions and actual green purchasing behavior. Methods: This study used a quantitative approach, with an online survey conducted using Google Forms and a structured questionnaire survey conducted with 201 respondents, who were selected using purposive sampling. The data was analyzed using Structural Equation Modeling (SEM) to understand the relationships between TPB components and green purchase intentions (GPI), with a consideration of how price sensitivity (PS) influences the correlation between GPI and GPB. Findings: The findings indicate that all three components of TPB were significantly and positively correlated with GPI, with green attitudes (GA) playing a dominant role. Moreover, GPI was also a significant factor influencing GPB. The study also reveals that PS had no moderation effect in the relationship between GPI and GPB. Conclusion: Strengthening green attitudes (GA), leveraging subjective norms (SN), and enhancing perceived behavioral control (PBC) can increase coffee purchase intentions in sustainable coffee shops. Greater intentions also increase the adoption of consumer behavior in purchasing coffee products in sustainable coffee shops. Research Implications: Point Coffee Yogyakarta can offer premium products that highlight the environmental value to differentiate itself from competitors, enhancing service and product quality to minimize low consumer sensitivity.